BISNIS KAUM SANTRI: Studi tentang Kegiatan Bisnis Komunitas Tarekat Qadiriyah Naqsyabandiyah Pekalongan - Muhammad Shulthoni; Misbakhudin; Nalim; Dewi Puspitasari (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2011)
To obtain a comprehensive study, I will see the Sufi orderís wisdoms implemented by the adherents of Qadiriyyah Naqshbandiyyah order of Pekalongan ñ by using Weberís theory the spirit of capitalism ñ in order to achieve their economic activities. In addition, how the Is-lamic teachings (tarekat ethics) are transforming their business. In an attempt to bring to the surface of the ethics in economic activities, this study will examine the orderís teachings practiced by the adherents of Qadiriyyah Naqshbandiyyah order of Pekalongan in one period of field research from June to October 2010. This is done by means of a process ñ as objective as possible ñ of description and interpretation. As I study my primary resources (from the books, magazines, websites, and interviews), my attention is focused on the treatment of the sub-ject, how the orderís ethics are articulated, and the way in which they function to observe the religious teachings in their business activities. This paper will explain social and historical background of Qadiriyyah Naqshbandiyyah order of Pekalongan, decribe the teachings and prac-tices which are implemented by the adherents, and finally clarify the influence of its teachings into the business activities of the adherents.